Urban Disaster Management in Government Communication Perspective - Jumansyah Jumansyah; Anwar Alaydrus; Budiman Budiman; Bebika Alamsyah (Kanal: Jurnal Ilmu Komunikasi, 2021)
One indicator of the success of regional governance is the ability of local governments to provide security and comfort for people from natural and social disasters, thus through the authority and resources of the local government they are required to build horizontal and vertical communication in order to respond and provide alternative solutions to all potential disaster that can cause material or non-material loss to the community. Therefore, this study aims to explore disaster management in the perspective of government communication in Botang City. This study used a qualitative case study approach with interactive analysis, so it was found that government communication in Bontang City was built through territorial, program and business approaches. So that the community and the private sector are actively involved in the disaster management process through coordinated communication under the command of the local government. In addition, communication between the local government of Bontang City in disaster management is also continuously improved through active involvement of experts / experts, mass media, and community organizations / NGO / associations.